Two Mode DPM Equipped with an Automatic Leak Test Using MPX5050GP and MPXV4115VC6U Sensors - Fita Florensa Rooswita; Triana Rahmawati; Syaifudin Syaifudin (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
The calibration process aims to guarantee measurement results in accordance with established standards. One of the tools used for pressure calibration is the Digital Presure Meter, which is the function of this tool to measure pressure on the Sphygmomanometer and Suction Pump or other tools that use pressure parameters for measurement. This module uses the Arduino system as a control and processing of analog data into digital data in order to condition the output of the MPX5050GP sensor for positive pressure and MPXV4115VC6U sensor for vacum pressure, this module uses a 4x20 LCD character display and there is a selection of mmHg and Kpa units with fluctuating resolution 0.25. Also in this module there is also an automatic leak test feature for the Sphygmomanometer, the measurement results obtained an average error of 7.3 mmHg for sphymomanometer measurements, and for suction pumps less than 1.5 Kpa. From these results it was concluded that this module can be used for the measurement of tools that use positive pressure and negative pressure.